Male Pseudohermaphrodite With Uterus In Scrotum - Dr. Yadava Vishwa Nath Sahai; Dr. Dubey Surya Prakash; Dr. Saxena Santosh Kumar (Indian Journal of Plastic Surgery)
An unusual case of a male pseudohermaphrodite where uterus with its fallopian tubes and both the testes with their vas deference were present on one side only, has been presented. The gonadal abnormality was found to be associated with oblique inguinal hernia on the same side.